A study of the 46-year-old Arrow oil spill: Persistence of oil residues and variability in oil contamination along Chedabucto Bay, Nova Scotia, Canada. (10th October 2018) - Yang, Zeyu; Shah, Keval; Laforest, Sonia; Hollebone, Bruce P.; Lambert, Patrick; Brown, Carl E.; Yang, Chun; Goldthorp, Michael
Abstract: The occurrence, spatial distribution and source of petroleum-related hydrocarbons, and the degree of weathering of Arrow oil residues persisting on the shoreline of Chedabucto Bay, Nova Scotia, were assessed. The hydrocarbons assessed included total petroleum hydrocarbons (TPH), n -alkanes from n- C 9 to n- C 40, petroleum biomarkers like terpanes, hopanes and steranes, non-alkylated polycyclic aromatic hydrocarbons (PAHs) and their alkylated homologues (APAHs). Trapped Arrow oil in the sunken tanker has not experienced any marked weathering. The collected environmental samples could be classified into three groups. Group 1 samples were oil free identified by low TPH, highly resolved fractions, a predominantly biogenic source of n -alkanes, and trace amounts of petroleum biomarkers probably from the historical (1970) oil spill. Group 2 samples had higher TPH and the other targets than Group 1 samples. The mixed petrogenic and terrestrial plant inputs were the source of n -alkanes, while the pattern of APAHs indicated that their source varied from site to site, being either recently released petroleum or Arrow oil residues. Group 3 samples mainly contained oil residues from Arrow oil spill, having very high levels of TPH, APAHs and biomarkers; however, most samples were free of n -alkanes. Group 3 samples were mostly found on the southern shoreline of Chedabucto Bay, especially in the upper to middle intertidal zone of the shorelines characterized by mixed pebble/cobble/boulders. The extent of weathering of n -alkanes and APAHs showed no relation to each other, although n -alkanes were depleted more fully than APAHs for most of the oil residues. Thus, various natural attenuation processes, especially for microbial degradation, have contributed to the aging of these oil residues. The degree of weathering varied with different environmental conditions. Highlights: Samples could be classified into oil free, relatively clean and Arrow oil residues. Source of oil varied from sample sites. Abundant oil residues were found in the pebble/cobble/boulder shoreline. Dominant micro-degradation processes contributed to the aging of oil residues. Environmental conditions are crucial for the weathering of oil residues.